Seasonal changes in submarine melting mechanisms controlling frontal ablation of Hansbreen, Svalbard - Michał Ciepły; Dariusz Ignatiuk; Mateusz Moskalik; Jacek Jania; Bartłomiej Luks; Oskar Głowacki; Kacper Wojtysiak (Journal of Glaciology)
We describe the annual pattern of frontal ablation driven by submarine melting mechanisms at the Hansbreen terminus: these are reflected in the intensity and spatial distribution of calving events. Analysis of time-lapse images of the Hansbreen front in conjunction with oceanographic and meteorological data shows that calving intensity is driven primarily by seawater temperature. Regression analysis also highlights the importance of air temperature, which we take to be a proxy for surface ablation and subglacial discharge. This, combined with seasonal changes in ice cliff tortuosity and the increasing significance of wave motion outside the ablation season, enabled us to determine seasonal changes in the mechanisms of ice cliff undercutting by submarine melting. While submarine melting controlled by estuarine circulation primarily drives frontal ablation in summer, wave-driven melting at the waterline is more important outside the ablation season. During winter, ice cliff undercutting by melting is suspended by low seawater temperature, negligible subglacial water discharge and sea-ice cover. The most intense frontal ablation, recorded in summer, was related to higher sea temperature and vigorous estuarine circulation.